Pelatihan Metodik dan Didaktik Pembelajaran Bahasa Jerman bagi Guru Bahasa Jerman di Kota Ambon - Soumokil, Piet; Lestuny, Carolina; Tomasouw, Jolanda; Wenno, Eldaa Crystle (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2024)
This Community Service activity aims to improve the pedagogical competence of German language teachers in Ambon City in the methodical and didactic aspects of German language learning. This training is motivated by the need for teachers to develop teaching skills that are effective, innovative, and relevant to curriculum developments and student needs. The methods used in this training include lectures, interactive discussions, simulations, and hands-on practice in preparing and implementing lesson plans based on communicative methods and task-based learning approaches. The training was attended by 20 German language teachers from various secondary schools in Ambon City. The results of this activity show an increase in participants' understanding of the methodical and didactic concepts of German language learning, which is reflected in their success in developing creative and student-centered lesson plans. In addition, participants were also able to apply various learning strategies that support students' mastery of language competencies, such as the selection of appropriate exercises and tasks in accordance with learning objectives (Rückwärtsplannung). The conclusion of this activity is that the methodic and didactic training of German language learning significantly helps teachers in developing more effective and interesting teaching skills. Recommendations from this activity are the need for further training to explore the implementation of technology-based learning methods and collaboration between teachers to support innovation in German language learning in schools.